2008
DOI: 10.1016/j.schres.2007.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Histone deactylase 1 expression is increased in the prefrontal cortex of schizophrenia subjects: Analysis of the National Brain Databank microarray collection

Abstract: Histone deactylase enzymes are responsible for the deacetylation of histone tails, and consequently influence gene regulation through their ability to modify chromatin structure surrounding promoter regions. We analyzed the microarray collection of the National Brain Databank to investigate differential expression of these enzymes in the prefrontal cortices of control, schizophrenia and bipolar subjects. HDAC1 expression levels were significantly higher in schizophrenia versus normal subjects. The mRNA express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(129 citation statements)
references
References 34 publications
5
123
0
1
Order By: Relevance
“…S1A). These data confirm previous results showing that Hdac1 is upregulated in postmortem brain samples from patients with schizophrenia (21,22) and provide further evidence that HDAC1 might play a role in the pathogenesis of neuropsychiatric diseases. Because deletion or overexpression of Hdac1 in all neurons of the mouse brain from prenatal stages did not cause any behavioral changes (23), we speculated that elevated HDAC1 levels in patients with schizophrenia may be due to environmental risk factors that drive Hdac1 expression in the postnatal brain, thereby limiting the effect of compensatory processes.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…S1A). These data confirm previous results showing that Hdac1 is upregulated in postmortem brain samples from patients with schizophrenia (21,22) and provide further evidence that HDAC1 might play a role in the pathogenesis of neuropsychiatric diseases. Because deletion or overexpression of Hdac1 in all neurons of the mouse brain from prenatal stages did not cause any behavioral changes (23), we speculated that elevated HDAC1 levels in patients with schizophrenia may be due to environmental risk factors that drive Hdac1 expression in the postnatal brain, thereby limiting the effect of compensatory processes.…”
Section: Resultssupporting
confidence: 92%
“…Our findings confirm previous studies that reported elevated Hdac1 expression in patients with schizophrenia (21,22). Together with our observation that overexpression of HDAC1 in neurons of the mPFC of mice leads to schizophrenia-like phenotypes, these data provide solid evidence for a role of HDAC in the pathogenesis of schizophrenia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It has been suggested that subjects with psychosis have histone marks characteristic of a restrictive chromatin state , such as reduced acetylated histone 3 , increased dimethylated lysine 9 of histone 3 (Gavin et al, 2009b), reduced methylated lysine 4 of histone 3 in female schizophrenics , and increased HDAC1 expression (Benes et al, 2007;Sharma et al, 2008). Although, Akbarian et al (2005) reported increases in an 'open' histone mark associated with reduced metabolic gene expression in SZ (Akbarian et al, 2005).…”
Section: Gadd45b and Psychosis Dp Gavin Et Almentioning
confidence: 99%
“…Notably, as discussed above, HDAC1 regulates extinction learning via a mechanism involving H3K9 deacetylation and the subsequent trimethylation of target genes [185]. Interestingly, HDAC1 was up-regulated in postmortem brain samples from schizophrenic patients [223,224]. Using a pharmacological approach with the PCAF activator SPV106 and the PCAF inhibitor (H3-CoA-20-Tat), these authors demonstrated that PCAF activity facilitated the formation of fear extinction memory, but was not essential for fear acquisition [219].…”
Section: In Vivo Effect Of Hat Activators On Brain Functionsmentioning
confidence: 97%